2008
DOI: 10.3928/08910162-20080601-02
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Toxicity of Artificial Sweeteners

Abstract: Since their discovery, the safety of artificial sweeteners has been controversial. Artificial sweeteners provide the sweetness of sugar without the calories. As public health attention has turned to reversing the obesity epidemic in the United States, more individuals of all ages are choosing to use these products. These choices may be beneficial for those who cannot tolerate sugar in their diets (e.g., diabetics). However, scientists disagree about the relationships between sweeteners and lymphomas, leukemias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 35 publications
0
88
0
6
Order By: Relevance
“…Nicotine has a high toxicity to humans, compared to other alkaloids and neonicotinoid pesticides, such as imidacloprid, are widely used. The toxicity of artificial sweeteners as food additives is reviewed by Grice and Goldsmith (2000) and by Whitehouse et al (2008).…”
Section: Lifestyle and Personal Care Productsmentioning
confidence: 99%
“…Nicotine has a high toxicity to humans, compared to other alkaloids and neonicotinoid pesticides, such as imidacloprid, are widely used. The toxicity of artificial sweeteners as food additives is reviewed by Grice and Goldsmith (2000) and by Whitehouse et al (2008).…”
Section: Lifestyle and Personal Care Productsmentioning
confidence: 99%
“…[10] Although artificial sweeteners have been welcomed into the food industry for its beneficial uses, some studies have found correlations between their use and illnesses such as cancers, hepatotoxicity, headaches, allergies, seizures, diarrhoea, and low birth weight. [9] Commercially available saccharin is almost 300-500 times sweeter than sucrose. [11] This artificial sweetener is probably one of the most scrupulously researched sweeteners since its discovery, with much of the focus pertaining to its potential role in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The manufacture of artificial sweeteners by the food industry, promised consumers the sweetness of sugar without the calories. [9] Diabetic patients and individuals wanting to control their weight have access to these products that allow them the pleasure of a sweettasting treat without adverse health effects. [1] These alternate sweeteners are used extensively as additives in food, beverages, confectionary, and in the pharmaceutical sector.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations